Law No. 20 of the year 2018 Amending Certain Provisions of Law No. 152 of the Year 1980 On Establishing the Egyptian National Railways Authority = قانون رقم 20 لسنة 2018 بتعديل بعض أحكام القانون رقم 152 لسنة 1980 بإنشاء الهيئة القومية لسكك حديد مصر - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic